Spatio-temporal dynamics of the carbonate system during macroalgae farming season in a semi-closed bay in southeast China - Zhang, Zhi; Wang, Feipeng; Lei, Lingyi; Zheng, Nan; Shen, Zhongyuan; Mu, Jingli (Frontiers in Marine Science, 2024)
Ocean Negative Carbon Emission encompasses not only measures in natural marine chemistry and biology but also the potential of mariculture in achieving carbon sink goals. Growing awareness of the interplay between aquaculture and coastal carbonate system has drawn researchers' attention amid rising CO2 concentrations and negative impacts of aquaculture on the environment. In this study, twelve sites representing different maricultural types were selected, including macroalgae, shellfish and fish and non-farming area. The environmental factors, dissolved inorganic carbon (DIC), total alkalinity (TA) and pCO2 were measured monthly during kelp farming periods. Nitrate is a major component of total nitrogen and NO3-N concentration in macroalgal culture zone was lower than others, indicating effective nitrogen removal by macroalgae aquaculture. TA and DIC in non-farmed area demonstrated larger variation ranges than in farming areas, probably due to effects of precipitation on salinity. Aquaculture activities effectively maintained TA and DIC, with macroalgae cultivation playing an important role in TA stability, potentially resisting acidification. The pCO2sea-air of macroalgae culture areas in spring was slightly negative, suggesting carbon sink potential. However, further research is needed to assess the full extent of this "fourth type" of blue carbon, including accurate carbon footprint calculation, and contributions of particulate organic carbon and recalcitrant dissolved organic carbon. This study provided insight into the comprehensive contribution of different aquaculture types to fishery environment and carbonate system, which can furthermore help guide aquaculture management and facilitate the carbon-neutral transition of aquaculture.